Index of potable water infrastructure resilence facing hurricanes in coastal cities - Martínez Méndez, Anita; Frausto Martínez, Oscar; Castillo Villanueva, Lourdes; Camacho Sanabria, José Manuel (Revista Geográfica de América Central., 2018)
The aim of this research was to determine the index of potable water infrastructure resilence facing hurricanes in a coastal city. The theoretical model is based on the 4R resilence and the adaptive capacity variable. To gather the data, a questionnaire was applied to the population, as a probabilistic sampling. Arcmap v. 10.3 was used to analyze the results in order to show the interurban spatial difference. Afterwards, some indicators were created and standarized according to their positive or negative effect in the resilence, which helped us to determine the index of the city as 0.69.